Digital platforms for smallholder credit access: The mediation of trust for cooperation in maize value chain financing. (1st November 2018) - Agyekumhene, Christopher; de Vries, Jasper R.; van Paassen, Annemarie; Macnaghten, Philip; Schut, Marc; Bregt, Arnold
Abstract: Maize production is of critical importance to smallholder farmers in Ghana. Various factors limit the productivity of smallholder maize farming systems undergirded by the lack of capital for critical investments both at the farm and at national policy levels. Using a value chain approach, this diagnostic study explains how a complex configuration of actor interaction within an institutionally and agro-ecologically challenged value chain leads to the enduring absence of maize farming credit support. We find a cycle of credit rationing resulting from value chain challenges such as agro-ecological uncertainties, inadequate GAPs training, weak farmer groups and market insecurity. This condition is sustained by an interplay between mistrust, insufficient information across the value chain and inadequate control strategies in the maize credit system. We argue that Digital Platforms (DPs) show potential to help overcome some information and communication gaps and related uncertainties that impede traditional value chain credit arrangements. This is promising in terms of aiding awareness and coordinated responsiveness to agro-ecological farm conditions and the development of farming records databases. Thus, DPs could generate new networks and forms of cooperation in the maize value chain in this regard. As a tool for mediating trust in value chain credit cooperation, strategic use of these DP contributions could help initiate an entry point for recalibration of trust perceptions. Significant considerations and improvements are however needed to harness DPs effectively in mediating trust for maize credit provision, not least being farmer digital inclusion in DP implementation, effective intermediation and network governance arrangements and digital contributions towards cost-effective agro-ecological controls in the erratic maize farming context. This approach to trust building should therefore not be viewed as a quick fix but as a process of trial and error, and learning by doing.